2018
DOI: 10.1002/aur.2053
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the chinese version of autism spectrum quotient‐children's version: A sex‐specific analysis

Abstract: A Simplified Chinese translation of the Autism Spectrum Quotient‐Children's Version (AQ‐C) is needed for research in mainland China. Autism Spectrum Disorder (ASD) is a condition that differs in presentation and prevalence by sex. Thus, evaluating the psychometric validity of the AQ‐C in males and females is an important step in its validation. The present study aims to develop a Chinese translation of the parent‐report AQ‐C, and test its psychometric properties among Mandarin Chinese speaking boys and girls. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Second, the AQ-Child includes items related to children's subjective, internal states, including imagination and mindreading, which parents may find difficult to report on. While previous studies showed adequate concurrent validity, good internal consistency and good test-retest reliability of the Mind-reading and/or Imagination subscales (Sun et al, 2019;Gomez et al, 2018), it would be worthwhile for future studies to examine differences in validity of the imagination/mindreading subscales and the social behavior subscales. Furthermore, study recruitment was not the same in both countries.…”
Section: Limitationsmentioning
confidence: 95%
See 3 more Smart Citations
“…Second, the AQ-Child includes items related to children's subjective, internal states, including imagination and mindreading, which parents may find difficult to report on. While previous studies showed adequate concurrent validity, good internal consistency and good test-retest reliability of the Mind-reading and/or Imagination subscales (Sun et al, 2019;Gomez et al, 2018), it would be worthwhile for future studies to examine differences in validity of the imagination/mindreading subscales and the social behavior subscales. Furthermore, study recruitment was not the same in both countries.…”
Section: Limitationsmentioning
confidence: 95%
“…Within ASD, males outnumber females with a sex ratio of 4.3:1 (Maenner, 2020). Previous studies found that boys with ASD are prone to isolation and thus less social (Hiller et al, 2015) and have more stereotyped and repetitive behaviors than girls (Hiller et al, 2015;Sun et al, 2019;Szatmari et al, 2012). Moreover, although ASD is generally considered a 'life-long' condition, the severity of core symptoms seems to increase or decrease as children grow older (Fountain et al, 2012;Louwerse et al, 2015;Scheeren et al, 2019).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Difficulties in processing different, often more general, contexts of a task are described by the weak central coherence theory (WCC), which addresses autistic individuals (Russell et al, 2019;Scher, Shyman, 2019). Second-arily, this can create a sense of overload and fatigue, and it some cases promote non-activity, withdrawal from task execution, failure to finish an activity or complete it on time (Sun et al, 2019).…”
Section: Personality Traits In the Bigmentioning
confidence: 99%